Perceptions Of Local Residents Towards Tourist Arrival On My02 Program - Nurul Farah Izzah Zailani; Abdul Rahman Redha Ahmad Rashidi; NurFatin Adila Md Diton (Universitas Internasional Batam, 2024)
MYO2 program name is derived from Oil and Oxygen (O2) and basically to give awareness to all of the danger by disposing used cooking oil and the importance of keeping our nature alive. MYO2 Program is a tree planting program that was organized by School of Hospitality & Creative Arts (SHCA), MSU Shah Alam and the main goal is to prevent plant photosynthesis and collect waste oil to make fertilizer for tree planting in Kanching Falls. Also, the program has been conducted in Kanching Falls, Rawang Selangor since 2018. It is our responsibility to embrace care for the environment towards sustainability. Therefore, this program also supporting four SDG’s which is SDG12 - Responsible Consumption and Production; SDG14 – Life below Water; SDG15 – Life on Land; and lastly SDG17 - Partnership for Goals where MSU has partnering with Shah Alam City Council and Tourism Selangor. The aim of this study is to find the linkage between visitors’ perception towards MYO2 Program that will be impact on value of attraction, facilities and service management and ecotourism activities. The findings were evaluated using SPSS and a quantitative approach was used. The total number of questionnaires distributed was 202. The respondents chosen were from the students of School of Hospitality and Creative Arts (SHCA) that participated in the program and visitors of Kanching Falls by using online questionnaires. A quantitative approach is used for this research by distributing online questionnaires to collect data from respondents. Also, the researcher disseminated the information through various channels in social media platforms. From the findings, facilities and services management has positive relationship towards visitor’s perception on MYO2 Program. At the end of this research, when it comes to visitors’ perception on MYO2 Program, researcher is becoming more interested in figuring out what are their perception.